Digital Learning Resource Sharing Platforms - Kumar, Yashavanth; Husein, Bhoomika Khaja (Journal of Research in Vocational Education, 2025)
This research paper presents the development and evaluation of a flutter based mobile application designed for the free-of- cost sharing of physical learning resources such as textbooks and notes. Unlike e-learning platforms that promote digital learning, this application emphasizes the physical circulation of educational materials within institutions and local communities. Built using Flutter for a lightweight and responsive user interface, the system integrates PHP-based back-end functionality and MySQL for data storage. The paper discusses the application's design, implementation, testing, and its potential impact on sustainable education